A mathematical model of catalyst combination design and temperature control in the preparation of C4 olefins through ethanol coupling. Issue 16 (4th April 2023) - Tang, Pengxiang; Li, Hongting; Zhang, Xiaomei; Sun, Xin
Abstract : The preparation of C4 olefins through ethanol catalytic coupling is a crucial area of study. Abstract : The preparation of C4 olefins through ethanol catalytic coupling is a crucial area of study. According to the experimental data obtained by a chemical laboratory for different catalysts at different temperatures, three mathematical models were developed to provide insights into the relationships among ethanol conversion rate, C4 olefins selectivity, yield, catalyst combination, and temperature. The first model is a nonlinear fitting function that analyses the relationships among ethanol conversion rate, C4 olefins selectivity, and temperature under varying catalyst combinations. Two-factor analysis of variance was employed to determine the influence of catalyst combinations and temperatures on ethanol conversion rate and C4 olefins selectivity. The second model is a multivariate nonlinear regression model that describes the relationships among the yield of C4 olefins, catalyst combination, and temperature. Finally, an optimization model was derived based on the experimental conditions; it provides a solution for the selection of the optimal catalyst combinations and temperatures to achieve the maximum yield of C4 olefins. This work has significant implications for the field of chemistry and the production of C4 olefins.